Phylogenetic Affiliation and Quantification of Psychrophilic Sulfate-Reducing Isolates in Marine Arctic Sediments - Sahm, Kerstin (American Society for Microbiology, 1999)
Thirteen psychrophilic sulfate-reducing isolates from two permanently cold fjords of the Arctic island Spitsbergen (Hornsund and Storfjord) were phylogenetically analyzed. They all belonged to the δ subclass of Proteobacteria and were widely distributed within this group, indicating that psychrophily is a polyphyletic property. A new 16S rRNA-directed oligonucleotide probe was designed against the largest coherent cluster of these isolates. The new probe, as well as a set of available probes, was applied in rRNA slot blot hybridization to investigate the composition of the sulfate-reducing bacterial community in the sediments. rRNA related to the new cluster of incompletely oxidizing, psychrophilic isolates made up 1.4 to 20.9% of eubacterial rRNA at Storfjord and 0.6 to 3.5% of eubacterial rRNA at Hornsund. This group was the second-most-abundant group of sulfate reducers at these sites. Denaturing gradient gel electrophoresis and hybridization analysis showed bands identical to those produced by our isolates. The data indicate that the psychrophilic isolates are quantitatively important in Svalbard sediments.